Adrenal Infarct as a Presenting Finding in Polycythemia Vera (PV) - Guruli, Marie (J Endocr Soc, 2021)
Adrenal infarct as a presenting finding in Polycythemia Vera (PV) Marie Guruli, Vitaly Kantorovich Background: While hemorrhagic adrenal infarcts, usually bilateral, have been described in hematologic malignancies, usually PV, no hemorrhagic variant are exceedingly rare. Here we describe a single case of unilateral nonhemorrhagic adrenal infarct. Case Presentation: 30-year- old male with past medical history of type 1 diabetes on insulin, presented with one day history of right upper quadrant (RUQ) abdominal pain. Initially pain was mild but slowly progressed to 10/10 intensity within the next several hours, felt like a sharp and stabbing pain with radiation up to the chest. Patient also reported to have difficulty breathing due to pain, along with nausea and vomiting. Laboratory results showed leukocytosis 11.2, H&H of 19.1/56.8, platelet count of 637, glucose of 283, alkaline phosphatase of 147. Abdominal ultrasonography reported nonspecific mild hepatomegaly and strongly suspected small thrombus within the IVC. Further work up included CTA study was negative for PE (pulmonary embolus), but MRI showed a filling defect in the suprarenal IVC along with right adrenal infarction. Patient was thermodynamically stable. Fortunately, cortisol was 21.3 and DHEA levels were 419, indicating no apparent effect on adrenal function. Patient underwent a bone marrow biopsy and was eventually diagnosed with PV. He was discharged in the stable condition with a close follow up with his endocrinologist for monitoring and repeat MRI for right adrenal infarct within the next few months. Conclusion: This case illustrates the importance to screen patients with PV who presented with similar clinical presentation for possible adrenal insufficiency. It also highlights the importance of undertaking imaging for careful consideration, close follow up to prevent life threatening complications and even death.